Head and neck - Pailin Kongmebhol (2018)
© Springer-Verlag Berlin Heidelberg 2015. Head and neck imaging is probably one of the most difficult subspecialties for radiologists. The small but detailed anatomy in the head and neck region is difficult to understand and remember. Pitfalls can occur in any of the processes, ranging from acquiring to reading of images. In this chapter, the author presents some of the common and rare pitfalls that may occur in the clinical practice. These pitfalls include normal variations and diseases of the temporal bone, paranasal sinuses, salivary glands, larynx, oral cavity, lymph nodes, and deep spaces of the neck. Some other conditions of the head and neck, such as neck mass, missed cancers, and posttreatment changes, are also discussed. Awareness of these potential pitfalls and knowledge of the normal head and neck anatomy can help radiologists to avoid misinterpretation.